Ubiquitination in lipid metabolism reprogramming: implications for pediatric solid tumors - Zhang, Weixin; Xu, Yile; Fang, Yingjin; Li, Meng; Li, Di; Guo, Huiqin; Li, Hang; He, Jing; Miao, Lei (Frontiers in Immunology, 2025)
Pediatric solid tumors represent a significant subset of childhood cancers, accounting for approximately 60% of new diagnoses. Despite advancements in therapeutic strategies, survival rates remain markedly disparate between high-income and resource-limited settings, underscoring the urgent need for novel and effective treatments. Lipid metabolic reprogramming is a fundamental hallmark of cancer, driving tumor progression, therapeutic resistance, and immune evasion through enhanced fatty acid uptake, increased de novo lipid synthesis, and activated fatty acid β-oxidation (FAO). Ubiquitination, a dynamic post-translational modification mediated by the ubiquitin-proteasome system (UPS), plays a crucial role in regulating lipid metabolism by modulating the stability and activity of key metabolic enzymes and transporters involved in cholesterol and fatty acid pathways. This review comprehensively examines the complex interplay between ubiquitination and lipid metabolic reprogramming in pediatric solid tumors. It delineates the mechanisms by which ubiquitination influences cholesterol biosynthesis, uptake, efflux, and fatty acid synthesis and oxidation, thereby facilitating tumor growth and survival. Furthermore, the review identifies potential UPS-mediated therapeutic targets and explores the feasibility of integrating ubiquitination-based strategies with existing treatments. By targeting the UPS to disrupt lipid metabolism pathways, novel therapeutic avenues may emerge to enhance treatment efficacy and overcome resistance in pediatric oncology. This synthesis of current knowledge aims to provide a foundation for the development of innovative, precision medicine approaches to improve clinical outcomes for children afflicted with solid tumors.